SOAR-Based MSME Competitiveness in Purworejo Regency - Cuk Jaka Purwanggono; Ratih Pratiwi (Enrichment : Journal of Management, 2022)
Conceptually the goal to be achieved in this research is to develop encouraging economic growth in Purworejo Regency, one way to achieve this is by developing local MSME businesses to be able to compete in the global market. In an effort to improve the economy through MSME businesses, the researchers used the perspective of preparing strategic planning for the development of Local MSMEs with Global Competitiveness Based on SOAR (Strengths, Opportunities, Aspirations, Results) Analysis in Purworejo Regency in an effort to improve entrepreneurial performance. SOAR analysis allows an organization to examine all its levels and functional areas. In addition, SOAR analysis also focuses on improving tactics and strategies that are being carried out, to overcome existing weaknesses and threats so that they can be used as a basis for developing strategic mapping and the formulation of KPI measurements to developing strategic initiatives that affect the potential for successful entrepreneurship of MSMEs in Purworejo Regency. The research method uses a population of all micro, small and medium enterprises (MSMEs) registered in Purworejo Regency by taking random and representative research samples by considering several research variables. The data collection procedure used primary data, namely interviews and direct observations, while secondary data were books, journals, and other literature related to the research topic. To analyze the problem of strategic issues using the ASTRID method (Actual, Specific, Transforming, Relevant, Innovative, Can be done). In-depth analysis is carried out using SOAR analysis tools and Leavit's Model, because these analytical tools can describe conditions and problems as well as existing conditions, namely Structure, Technology, People and Task Analysis.